Social and educational exclusion in the community of the Greek-speaking Roma of Chalkida - Arvanitis, Nikolaos S. (The Greek Review of Social Research, 2019)
The doctorate thesis was elaborated at the Department of Philosophy, Pedagogy and Psychology of the University of Athens Philosophy Faculty, with a scholarship from the State Scholarship Foundation (IKY). It was supported in May 2018 and qualified as "excellent".